Effects of N-acetylcysteine treatment on ethanol's rewarding properties and dopaminergic alterations in mesocorticolimbic and nigrostriatal pathways - Laverde, Celina Ferrari [UNESP]; Morais-Silva, Gessynger [UNESP]; Amaral, Vanessa Cristiane Santana [UNESP]; Marin, Marcelo Tadeu [UNESP] (Wolters Kluwer, 2021)
Recent reports have shown that N-acetylcysteine (N-AC) has beneficial effects in the treatment of cocaine and nicotine abuse. Considering the similar neurobiologic mechanisms involved in the development of addiction to different drugs, N-AC treatment could be useful in the treatment of ethanol abuse. The rewarding properties of the drugs of abuse plays an important role in the development of addiction and can be studied using the conditioned place preference (CPP) paradigm. Thus, to study the effects of N-AC treatment in the rewarding effects of ethanol, we investigated the effects of N-AC administration in the ethanol-induced CPP and neurochemical alterations within the mesocorticolimbic and the nigrostriatal dopaminergic pathways. Adult male Swiss mice were pretreated with N-AC (60 or 120 mg/kg intraperitoneal) and tested for the development, expression, or extinction of the ethanol-induced CPP. Another cohort of animals received N-AC (60 or 120 mg/kg intraperitoneal) 2-h before an acute administration of ethanol and had their brains removed for dopamine and its metabolites quantification in the mesocorticolimbic and nigrostriatal pathways. Pretreatment with N-AC (120 mg/kg) blocked the development of ethanol-induced CPP. On the other hand, N-AC at both doses did not alter the expression nor the extinction of ethanol-induced CPP. N-AC increased 3,4-dihydroxyphenylacetic acid content in the medial prefrontal cortex and dopaminergic turnover within the substantia nigra. Besides that, there was an increase in dopamine content in the nucleus accumbens of ethanol-treated animals. In summary, N-AC treatment blocked the development of ethanol CPP, without altering ethanol effects on dopaminergic neurotransmission.
Keywords: addiction; conditioned place preference; cystine-glutamate antiporter; dopamine; ethanol; N-acetylcysteine; rat